Analisis Kemampuan Pemecahan Masalah Matematis Siswa SMP Dalam Menyelesaikan Soal Pisa Pada Konten Space And Shape Ditinjau Dari Gaya Belajar - Awwaliya, Sella ‘Izzata; Retnawati, Heri (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to analyze the mathematical problem solving ability of VIII grade students of SMPN 4 Pakem in the 2022/2023 school year in solving PISA adaptation problems on space and shape content in terms of learning style. Indicators of mathematical problem solving using Krulik and Rudnick's stages. This research is a descriptive qualitative approach. A total of 157 students filled out the learning style questionnaire and initial math test, then 45 students were selected, namely 15 students each type of learning style who would be given a test of PISA adaptation questions on space and shape content. Then 9 students were selected, namely 3 students each type of learning style to carry out interviews. Data validity used source triangulation. The data analysis used was data reduction, data presentation, and conclusion drawing. The results showed that the percentage of students with visual and auditory learning styles was the same at 29%, the percentage of students with kinesthetic learning styles was 19%, while the percentage of students with mixed learning styles was below 10% each. There are differences in the achievement of mathematical problem solving indicators of students with different learning styles even though the initial level of problem solving ability is the same. None of the subjects with visual, auditorial, and kinesthetic learning styles were able to solve the problem with the right answer and mathematical process on level 6 problems.